Increasing Teacher Professionalism through Learning Technology (Photo Novella, Learning Videos, E-Books, and E-Learning) at PGRI Cigedug District - Nasrulloh, Iman; Ismail, Yasir (Fakultas Kewirausahaan Universitas Garut, 2022)
This community service research aims to enhance teacher professionalism in PGRI Cigedug District through the utilization of various learning technologies, namely photo novela, instructional videos, e-books, and e-learning platforms. The background of this activity lies in the limited digital literacy and technological mastery among teachers, while the Merdeka Curriculum requires innovation, flexibility, and differentiated learning. The research employed a descriptive-analytical method by conducting training, mentoring, and hands-on practice designed to enable teachers to produce and implement technology-based learning media. The results show a significant improvement in teachers’ skills, particularly in creating interactive media, utilizing digital platforms, and integrating technology into student-centered learning. Teachers who previously relied on conventional teaching methods began to shift their paradigm toward more creative and innovative approaches. Photo novela was proven effective in fostering students’ reading literacy, instructional videos facilitated the delivery of complex concepts, e-books provided wider access and learning flexibility, while e-learning supported digital classroom management despite infrastructural limitations. These findings highlight that the integration of learning technology is an essential strategy to strengthen teacher competence as well as the overall quality of education in the digital era. Sustaining this program requires continuous institutional support, intensive training, provision of adequate infrastructure, and the establishment of teacher learning communities.